1999
DOI: 10.1017/s1355838299982195
|View full text |Cite
|
Sign up to set email alerts
|

The folding of large RNAs studied by hybridization to arrays of complementary oligonucleotides

Abstract: Folding pathways of large RNAs are poorly understood. We have addressed this question by hybridizing in vitro transcripts, which varied in size, to an array of antisense oligonucleotides. All transcripts included a common sequence and all but one shared the same start-point; the other had a small deletion of the 59 end. Minimal free energy calculations predicted quite different folds for these transcripts. However, hybridization to the array showed predominant features that were shared by transcripts of all le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Experiments to measure the effect of different single-stranded nucleic acid structures, under high salt conditions, on the rate of duplex formation on solid supports, have shown that RNA or cDNA structural motifs may impede hybridization between probe and target and, therefore, bias the results obtained in gene expression arrays (49)(50)(51)(52). Here, we have reversed the argument and, by taking advantage of the solid support hybridization techniques, we have aimed at evaluating the structural degree of long RNA molecules with potential application to HCV diagnostics and therapeutics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments to measure the effect of different single-stranded nucleic acid structures, under high salt conditions, on the rate of duplex formation on solid supports, have shown that RNA or cDNA structural motifs may impede hybridization between probe and target and, therefore, bias the results obtained in gene expression arrays (49)(50)(51)(52). Here, we have reversed the argument and, by taking advantage of the solid support hybridization techniques, we have aimed at evaluating the structural degree of long RNA molecules with potential application to HCV diagnostics and therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…This makes some sequences to remain accessible to further longrange interactions, while others show restricted accessibility to distant regions. As elongation of the RNA chain proceeds, more structures are added to the transcript which could mask the accessible sites previously obtained (51). Therefore, one should be cautious when interpreting accessible positions, since long-range interactions may involve not only the ends of an RNA transcript but also its internal regions, otherwise revealed by the loss of hybridization signals that results from extending the transcript length.…”
Section: A First Approach On Macroarraysmentioning
confidence: 99%
“…This procedure was successful in identifying accessible regions on the mRNAs encoding β-globin, RhoA and luciferase (Zhang, Mao et al 2003). Microarrays were developed to examine the structure of an mRNA over a range of about 100 nt (Milner, Mir et al 1997;Sohail, Akhtar et al 1999;Sohail and Southern 2000). These arrays are produced using an innovative approach to We analyzed the accessible sequences on Lcn2 mRNA by both tiled microarray and computational methods to identify optimal AS-ODNs.…”
Section: Discussionmentioning
confidence: 99%
“…We have described a method to identify RNA sites that are favorable for hybridization with random oligonucleotide libraries and extension by reverse transcriptase, and have called them extendible sites+ The first question to ask is what is the relationship between extendible sites and RNA accessible sites described in the literature+ Accessible sites are loosely defined as those regions on an RNA molecule that can form stable complexes with complementary oligonucleotides+ However, conditions under which this stability is achieved as well as the length of the oligonucleotides used for analysis can significantly vary in different methods+ In one of the first methods (Hogenauer, 1970;Lewis & Doty, 1970;Uhlenbeck et al+, 1970;Uhlenbeck, 1972), RNA accessible regions were identified by using equilibrium dialysis to measure the association constants for the hybridization of 3-and 4-mer oligoribonucleotides to complementary regions of tRNA+ The tri-and tetranucleotides used in these studies are possibly the shortest oligonucleotides that can be employed for RNA probing, because 3-4 nt is the minimal size of a stable duplex corresponding to a nucleation complex (Craig et al+, 1971;Porschke & Eigen, 1971)+ Therefore, very short oligonucleotides bind to RNA regions that are not only in a single-stranded conformation, but are also flexible enough to adopt a duplex conformation upon binding (Uhlenbeck et al+, 1970)+ On the other side of the length spectrum, hybridization with arrays of oligonucleotides (Milner et al+, 1997;Mir & Southern, 1999;Sohail et al+, 1999) generally employs much longer probes+ Although the method can analyze oligonucleotides ranging from 1 to 21 nt, optimal binding is usually achieved with 12-to 17-mers+ Because accessible regions of such length do not likely appear frequently in RNA structures, the assumption is that long oligonucleotides initiate binding at short regions that are sterically accessible for nucleation, and the heteroduplex subsequently propagates into more structured RNA regions+ Kinetic restrictions on the perturbations of RNA secondary structure at the oligonucleotide binding site may explain the long hybridization times (3-18 h) used in this method+…”
Section: Discussionmentioning
confidence: 99%